2020
DOI: 10.1161/circheartfailure.120.007503
|View full text |Cite
|
Sign up to set email alerts
|

How Patients With Heart Failure Perform Daily Life Activities

Abstract: Background: Cardiopulmonary exercise test and 6-minute walking test are frequently used tools to evaluate physical performance in heart failure (HF), but they do neither represent activities of daily living (ADLs) nor fully reproduce patients’ symptoms. We assessed differences in task oxygen uptake, both as absolute value and as percentage of peak oxygen consumption (peakVO 2 ), ventilation efficiency (VE/VCO 2 ratio), and dyspn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…However, there was a significant reduction in the cumulative time required to perform those activities characterized by a non-fixed duration (ADL 1-4 and ADL6, Figure 1) and a reduction in maximal heart rate in ADL1 and ADL3. This is well in line with the already quoted findings from Gary (Gary et al, 2011) and supports the hypothesis of Mapelli that, to perform a given exercise, patients with HF spontaneously adapt to the task by self-regulating the effort intensity through a time prolongation (Mapelli et al, 2020). Indeed, CR, by improving physical function and muscle deconditioning ended up in a reduction of the time needed to perform those ADLs like getting dressed, folding towels, or making a bed for which there was no limit in time duration.…”
Section: Effects Of Cardiac Rehabilitation On the Metabolic Requirements Of Adlssupporting
confidence: 92%
See 3 more Smart Citations
“…However, there was a significant reduction in the cumulative time required to perform those activities characterized by a non-fixed duration (ADL 1-4 and ADL6, Figure 1) and a reduction in maximal heart rate in ADL1 and ADL3. This is well in line with the already quoted findings from Gary (Gary et al, 2011) and supports the hypothesis of Mapelli that, to perform a given exercise, patients with HF spontaneously adapt to the task by self-regulating the effort intensity through a time prolongation (Mapelli et al, 2020). Indeed, CR, by improving physical function and muscle deconditioning ended up in a reduction of the time needed to perform those ADLs like getting dressed, folding towels, or making a bed for which there was no limit in time duration.…”
Section: Effects Of Cardiac Rehabilitation On the Metabolic Requirements Of Adlssupporting
confidence: 92%
“…Moreover, for ADLs not requiring a fixed execution time, chronic HF patients needed more time to complete them ( Spruit et al, 2011 ). Mapelli et al (2020) studied 60 patients with HF and 40 healthy volunteers and confirmed the importance of prolongation of exercise time during ADLs with no fixed duration, as a means to reduce metabolic cost and optimize effort. Notably, patients with severe HF had a greater prolongation of exercise with respect to patients with less severe HF ( Mapelli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Healthy adults rarely reach high levels of activity during daily activities that would incite exertion [ 10 ]. In contrast, patients with chronic heart failure (HF) reach maximum load and exertion more often in their daily lives, and they frequently adapt by decreasing intensity and prolonging the effort [ 11 ]. Hence, it is important to assess the potential effects of different face masks in these patients.…”
Section: Introductionmentioning
confidence: 99%